STRATEGI ALIANSI QUADRILATERAL SECURITY DIALOGUE (QUAD) DALAM MENANGGAPI ESKALASI KONFLIK LAUT CHINA SELATAN (TAHUN 2020-2024) - Milda, Meylani Cesarah; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research analyzes the response of the Quadrilateral Security Dialogue (Quad) alliance to the escalating tensions and conflict in the South China Sea—an area of strategic importance within the broader Indo-Pacific region, which holds significant value due to its diverse natural resources. The focus of this study is on the strategic initiatives taken by the Quad, a group of Indo-Pacific-based countries, in addressing the conflict escalation in the South China Sea, a region considered vital for international security and stability. This research employs a qualitative method through literature review, sourcing data from books, documents, reports, journals, newspapers, articles, and online publications. The study adopts the perspective of Neorealism and the theory of Maritime Security. The study finds that the Quad has implemented various strategic initiatives to respond to potential threats and escalating conflict in the South China Sea, aimed at preserving regional stability and security. These initiatives include joint Malabar exercises, cooperation in coast guard patrols, and maritime surveillance through satellite and radar technologies. However, it is important to emphasize that the Quad’s approach is supportive rather than dominant, respecting ASEAN’s centrality in the regional maritime security discourse. Keywords: Maritime Security, Conflict Escalation, South China Sea, Strategy, Quadrilateral Security Dialogue